Simulation features of ground vehicle stabilizer with digital control unit - Сущенко, О.А.; Маляров, С.П.; Сайфетдінов, Р.А.; Янкелевич, Г.Є. (Proceedings of National Aviation University (archive), 2010)
Simulation features and results of ground vehicle stabilizer with digital regulator are studied. The way of its sampling is defined. The digital-analog and analog-digital converters models are represented. The simulation results are represented.